TEACHING TECHNIQUE IN IMPROVING STUDENTS' VOCABULARIES THROUGH SONGS: A LITERATURE REVIEW - Brylialfi Wahyu Furidha (SUJANA: Education and Learning Review, 2022)
There are two objectives of this research, these are (1) to find out techniques in teaching vocabularies; and (2) to analyze the techniques in teaching vocabulary using songs as teaching media by literature review from several previous researches. The method used descriptive reviews method. This research analysis used literature review which is an important factor to take into consideration. It is an analysis that typically includes an outline, an explanation, and a critical assessment of previous research. Based on the research results, the researcher can decide that there are various techniques in teaching vocabulary from the previous researches, but there are three main activities are demonstrate the song verbally or non-verbally; use illustrations to describe the lyrics, such as pictures; and use their native language to convey the meaning of the vocabulary. Then, the main purpose is these teaching techniques are appropriate and suitable for students because there are various learning styles and characters in students.